2017
DOI: 10.1111/2041-210x.12769
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating intraspecific trait variation into functional diversity: Impacts of selective logging on birds in Borneo

Abstract: Summary As conservation increasingly recognizes the importance of species’ functional roles in ecosystem processes, studies are shifting away from measuring species richness towards measures that account for the functional differences between species in a community. These functional diversity (FD) indices have received much recent attention and refinement, but their greatest limitation remains their inability to incorporate information about intraspecific trait variation (ITV). We use an individual‐based mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 53 publications
(126 reference statements)
1
33
0
Order By: Relevance
“…We selected 15 functional traits previously recognized to be functionally important in the partitioning of niche space based on resource requirements, foraging substrate use and dietary composition (Sekercioglu, ). Trait data were collected from Wilman et al () and Del Hoyo, Elliott, Sargatal, Christie, and Juana () following methods in Ross et al (), and no traits were assumed a priori to contribute more to ecosystem functioning than others (for a full list of traits and their sources, see Table S1). We first down‐weighted correlated traits and scaled continuous traits (body mass and clutch size) so they approximated a Gaussian distribution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected 15 functional traits previously recognized to be functionally important in the partitioning of niche space based on resource requirements, foraging substrate use and dietary composition (Sekercioglu, ). Trait data were collected from Wilman et al () and Del Hoyo, Elliott, Sargatal, Christie, and Juana () following methods in Ross et al (), and no traits were assumed a priori to contribute more to ecosystem functioning than others (for a full list of traits and their sources, see Table S1). We first down‐weighted correlated traits and scaled continuous traits (body mass and clutch size) so they approximated a Gaussian distribution.…”
Section: Methodsmentioning
confidence: 99%
“…(2014) and Del Hoyo, Elliott, Sargatal, Christie, and Juana (2017) following methods in Ross et al (2017), and no traits were assumed a priori to contribute more to ecosystem functioning than others (for a full list of traits and their sources, see Table S1). We first down-weighted correlated traits and scaled continuous traits (body mass and clutch size) so they approximated a Gaussian distribution.…”
Section: Functional Diversitymentioning
confidence: 99%
“…Bennett et al ., ), as well as animals (e.g. Ross et al ., ) including terrestrial arthropods. Studies on wild bee communities have shown that intraspecific variation in body size may shape assembly along climatic gradients (Classen et al ., ), and mediate the effects of habitat fragmentation on community structure and the ecosystem function of pollination (Warzecha et al ., ).…”
Section: How Can Trait‐based Studies Address Outstanding Assumptions mentioning
confidence: 99%
“…, Ross et al . ). Yet these relationships may not be so one‐dimensional; in some cases, habitat fragmentation and selective logging have been found to have neutral or even positive relationships with certain components of biodiversity, particularly after a recovery time of several decades (Azevedo‐Ramos et al .…”
mentioning
confidence: 97%
“…Habitat fragmentation and selective logging have frequently been shown to reduce biodiversity across a range of taxa (Heydon & Bulloh 1997, Ewers et al 2015, Hamer et al 2015, Ross et al 2017). Yet these relationships may not be so one-dimensional; in some cases, habitat fragmentation and selective logging have been found to have neutral or even positive relationships with certain components of biodiversity, particularly after a recovery time of several decades (Azevedo-Ramos et al 2006, Gunawardene et al 2010, Edwards et al 2013.…”
mentioning
confidence: 99%